Management of Full Thickness Traumatic Macular Hole In An 7-Year-Old Boy : A Case Report: Poster Presentation - Case Report - Ophthalmologist - Amin, Ramzi (Majalah Oftalmologi Indonesia, 2023)
Introduction : Traumatic macular hole (TMH) formation is uncommon, usually occurs in young males, and the incidence varies in the literature from 1 to 9%.The study by Chen et al reported that early vitrectomy resulted in significantly higher rate of TMH closure compared to initial observation (100% vs 66.7%, respectively) Case Illustration : A 7yo boy presented with diminution of vision in right eye (RE) of 2 months duration.There was history of trauma on the right eye. Visual acuity (BCVA) was 6/60 and 6/6 in RE and LE (Left Eye) respectively.Dilated fundus examination of OD revealed a full thickness macular hole (FTMH). SSOCT of OD confirmed the presence of an FTMH (with minimal hole diameter of 850 microns) with cystoid changes at the edges.The patient underwent vitrectomy followed with ILM peeling and advised facedown position for a week. At postoperative week one, BCVA was improved 6/9. SSOCT showed type 3 hole closure. BCVA improved to 6/7.5 at 1 months. Discussion : The study by Chen et al. was the first multicenter, prospective, comparative case study that attempted to address the outcomes of patients with TMHs comparing observation to early vitrectomy. Authors reported that early vitrectomy resulted in significantly higher rate of TMH closure compared to initial observation (100% vs 66.7%, respectively). The child in our case was resulted in good outcome. Conclusion : Early vitrectomy in full thickness traumatic macular hole in a young age resulted the good outcome.